Histopathological and Clinicopathological Co-Relation of Non-Neoplastic Cystic Lesions in Surgically Removed Ovaries - Patel, Dipti Manojbhai; Baxi, Seema N (Annals of Pathology and Laboratory Medicine, 2020)
Introduction: Neoplastic ovarian lesions have been extensively studied, but less attention is paid to non-neoplastic cystic lesions. Though follicular cysts are the most common of the non-neoplastic cysts, the % of occurrence of individual non-neoplastic lesions is not known. Also, often there is dilemma in reporting the exact type of nonneoplastic cyst. This study was planned with the objectives of assessing percentage of non neoplastic cystic ovaries, determining the morphological forms and relation of the various cysts with age of patient, and to detect whether multicystic non neoplastic lesions are more frequent in present day. Materials and methods: A prospective hospital based cross sectional non-neoplastic ovarian cysts study was done between January to June 2019 in a tertiary hospital. All hysterectomy specimens with the accompanying ovary/ovaries and oophorectomy specimen were included. Microscopic features were assessed. Data was tabulated in MS excel sheet. Percentage of occurrences of age, size, morphological type, laterality and complaints were calculated. Result:50% of 193 ovaries had non neoplastic cystic lesions. Non neoplastic cysts were associated with fibroid in 54%, DUB in 17% and adenomyosis in 16% cases. They were seen commonly during reproductive age group(83%). Post-menopausal age showed 16% cases. 86% of the non neoplastic ovarian cystic lesions were unilateral. 20% non neoplastic cystic lesions were of <1cm, 74% were 1-5 cm in size and 5% were larger than 5 cm. Morphologically 40% were follicular lesions, 32% were simple serous cysts, 14% were haemorrhagic cysts, 8% corpus luteal cysts and 2% each theca lutein and epithelial inclusion cysts. Conclusion: Non neoplastic cystic ovaries comprised 50% of all ovarian lesions, 83% were seen during reproductive age group. Leiomyoma, dysfunctional uterine bleeding and adenomyosis were the common clinical features and 70% of the cysts were 1-5 cm in size. There was no relation between morphological types of the cystic lesions and functional status. Simple serous cyst, cystic follicle, follicular cyst, cystic corpus luteum, corpus luteal cyst, theca luteal cyst, epithelial inclusion cyst and haemorrhagic cyst were found of which follicular cyst was the commonest (40%) Multicystic non neoplastic lesions or polycystic ovaries were not found during the period of study.